Understanding the human performance envelope using electrophysiological measures from wearable technology - Nixon, Jim; Charles, Rebecca (Springer, 2017)
In this article, we capture electrophysiological measures from a new wearable technology to understand the human performance envelope. Using the NASA Multi-Attribute Task Battery (MATB II), participants completed tasks associated with flight control which included communication, tracking and system and resource monitoring. Electrophysiological measures relating to cardiac activity and respiration were taken using the new wearable technology. Our results show significant differences in both heart rate and respiration rate in response to different taskloads and that higher taskloads were associated with higher mental workload. Frequency measures of heart rate variability discriminated different task types but not taskloads. This finding may be related to differences in task complexity being more important than the number events which we have used to manipulate taskload. We suggest that this new generation of wearable sensors could be used to inform operator locus in a human performance envelope, indicating when assistance by the aircraft or another crew member may be necessary to maintain safe and efficient performance.
Keywords: Human performance envelope; Mental workload; Wearable; Taskload; Aviation; MATB